2018
DOI: 10.1111/jerd.12378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adhesive used as modeling liquid on the stability of the color and opacity of composites

Abstract: This study evaluates whether using adhesive systems for modeling a composite affects the color and opacity changes caused by staining solutions followed by a bleaching procedure. The findings suggest that the use of a universal adhesive as modeling liquid can reduce the alterations in optical properties caused by staining solutions, and the application of high-concentrated hydrogen peroxide over the composite reduce the color changes without fully recover the initial color.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 26 publications
1
34
1
4
Order By: Relevance
“…WI D , which is based on CIELAB color coordinates, was designed exclusively for dentistry and presented better correlation to visual perception of tooth whiteness, when it was compared with other indexes . Although this index has been recently published, it has already been cited in some studies, but it has not been used to compare bleaching treatments.…”
Section: Discussionmentioning
confidence: 99%
“…WI D , which is based on CIELAB color coordinates, was designed exclusively for dentistry and presented better correlation to visual perception of tooth whiteness, when it was compared with other indexes . Although this index has been recently published, it has already been cited in some studies, but it has not been used to compare bleaching treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The color parameters were measured over white background (L*white 85.6, a*white 1.28, b*white 6.83) while the opacity was directly measured by the device. To measure opacity, samples were made against white, black (L*black 26.32, a*black -38, b*black 0.53), and white backgrounds again (11). The spectrophotometer was adjusted for three consecutive readings, which were later averaged.…”
Section: Immersion Of Coffee and Color Stability Measurement (N=5)mentioning
confidence: 99%
“…Consequently, the discoloring agents were prevented from penetrating the inner surfaces. Similarly, Araujo et al (9) evaluated the effect of modeling resins on the color change and opacity of composites and concluded that the modeling resin did not affect the color. In the current study, the use of modeling resin was observed to have a positive effect on the color change.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the fact that adhesive resins that are used as the modeling liquid comprise hydrophilic monomers and the negative effect of solvents on the color stability of the composite has resulted in the search for a new, alternative method (8). Previous studies have supported the use of solvent-free adhesives containing higher proportions of hydrophilic resin, which can be selected as the modeling liquid (9).…”
Section: Introductionmentioning
confidence: 99%